Factors influencing the development of bone starvation syndrome after total parathyroidectomy in patients with renal hyperparathyroidism - Peng, Xuyang; Xia, Xiaofang; Li, Zhouting; Cheng, Feng; Zhu, Xi (Frontiers in Surgery, 2022)
Purpose: To investigate the factors affecting the development of bone starvation syndrome (HBS) after total parathyroidectomy in patients with renal hyperparathyroidism (SHPT). Patients and methods: The clinical data and perioperative indices of 141 patients who underwent PTX for SHPT were retrospectively analyzed. The patients were divided into HBS and non-HBS groups based on postoperative minimum blood calcium <1.87 mmol/L. The differences in general clinical data and perioperative related indices between the two groups were compared; logistic regression analysis was performed to analyze the risk factors influencing HBS occurrence after surgery. Multiple linear regression method was used to analyze the factors influencing the maintenance time of intravenous calcium supplementation and total amount of calcium supplementation during intravenous calcium supplementation. The correlation between Lg-Preoperative ALP and postoperative calcium level was analyzed using univariate linear regression, and the threshold value for the diagnosis of HBS was analyzed using the ROC subjects' working curve. Results: HBS occurred in 46 (32.6%) patients. Univariate analysis showed statistically significant differences in dialysis age, preoperative calcitonin, preoperative parathyroid hormone, preoperative blood phosphorus, and preoperative alkaline phosphatase between both groups (P<0.05). Logistic regression analysis using stepwise entry method concluded that preoperative alkaline phosphatase was an independent factor for the development of HBS after surgery. Preoperative parathyroid hormone was an independent factor for the duration of intravenous calcium supplementation and total calcium supplementation during intravenous calcium supplementation in the HBS group. Linear analysis showed that Lg-Preoperative ALP was negatively correlated with postoperative calcium level (r=0.3389, P<0.0001). Based on the ROC curve, for postoperative HBS, the cut-off ALP value was 199.5 U/L, with a sensitivity of 80.85% and specificity of 82.61%. Conclusion: Preoperative serum ALP may be an independent factor for HBS occurrence after surgery. When preoperative ALP >199.5 U/L, patients with SHPT are prone to HBS after surgery, and the higher the preoperative ALP, the higher the incidence of HBS, and vice versa. In addition, preoperative PTH may be the factor in the timing of postoperative intravenous calcium supplementation and the total amount of calcium supplementation during intravenous calcium supplementation in patients with HBS.